Successful Extubation Using Heliox BiPAP in Two Patients with Postextubation Stridor - Pragya Punj; Premkumar Nattanmai; Pravin George; Christopher R. Newey (Case Reports in Pulmonology)
Postextubation stridor is associated with significant morbidity. It commonly results in extubation failure after established medical treatment fails, such as nebulized epinephrine and/or intravenous steroids. The role of heliox (i.e., combination of helium and oxygen) in managing patients with postextubation stridor has not been fully established. We report two cases of postextubation stridor successfully treated with heliox delivered with bilevel positive airway pressure (BiPAP) after failure of standard medical therapy.